TRADISIONALIS-PURITAN DALAM POLEMIK KEAGAMAAN DI JAWA: Studi Terhadap Tāj al-Muslimīn karya KH. Misbah Mustofa - Muhammad Yunus; Muhammad Asif; Nehru Millat; Abdul Rosyid Minhaj (AL ITQAN: Jurnal Studi Al-Qur'an, 2025)
The discourse on religious polemics between modernist and traditionalist Muslims in Java has received more attention sociologically-anthropologically as well as in the discourse on Islamic thought in general. This study will investigate the religious polemic in the tafsir genre work, Tāj al-Muslimīn by KH. Misbah Mustofa (1919-1994), an interpreter who intensely involved himself in the discourse. Using critical discourse analysis, this study underlines that the Qur’anic exegesis was written in the midst of a fairly intense debate between modernists vis a vis traditionalist in the late 20th century in Java. The study also found that despite his traditional Javanese Muslim background, Misbach Mustofa was not only critical of the claims brought by modernists on issues such as ahlussunnah wa al-jama'ah, ijtihad and taklid and grave pilgrimage, but to some extent also sometimes critical of religious traditions and practices among traditional Muslims themselves. This attitude, for example, is shown in looking at the practices of Sufism and tariqat that are considered excessive. Misbach also likes to refer to the works of Ibn Taymiyah and Rashid Rida, which usually tend to be shunned among traditional Muslims in Java. He not only polemized with modernist figures but also with his own colleagues in traditional Muslims. This study contributes to showing the dynamics of modernist and traditional polemics even within its own internal circle. Furthermore, this study proposes a new typology in the discourse between modernist and traditional Muslims in Indonesia, namely traditionalist-puritan.